Aprendizagem probabilística de alunos do 7.° ano do ensino fundamental por meio de atividades de investigação - Socha, Rogério Ramos (2019)
This study aims to analyze the probabilistic learning of the students of the 7th of middle school and the contributions of a teaching practice guided by the problematization and investigation. This is a research with a qualitative approach through the case study which seeks to answer the question: what evidence of learning the probability of students in the 7th of middle school emerge when they carry out research activities? To do so, the construction of data was due to the development of investigative activities that involved random phenomena. Initially a survey was carried out to verify how the student perceives the probability and what he already knows about his concepts. From this, activities were developed that led the student to investigate randomness and uncertainty in situations related to reality in order to favor the development of probabilistic reasoning. The importance of these activities was evidenced by allowing the student to experience a rupture with the deterministic vision. In addition, the involvement and wide interaction of students in the development of activities was verified. It can be concluded that a practice based on investigative activities allowed students to clearly recognize the concepts of probability as well as opt for better choices in situations of uncertainty.